Global tourism, sustainable tourism & ecotourism: code of ethics, charter, guidelines, resolutions - Sinha, P.C. (ed.) (New Delhi, 2006)
The Book Gives An In-Depth Insight Into Contemporary Trends As, Far As Tourism Ethics , Charters,Guidelines And Resolutions Are Concerned. The Book Presents In Detail The World Tourism Organization'S Code Of?Ethics?For Tourism Sector In General And The Travelers. As Code Of Ethics For Travelers, A?Model?Guideline Developed By The Last Frontiers For Responsible Tourism In?Latin?America?Is Dealt In Detail.A Complete Overview Of The State Of Affairs Existing The Global Sustainable Tourism Is Briefly Discussed. The Charter For Sustainable Tourism Development At The World Conference On Sustainable Tourism In?Spain?During 1995 And The United?Nations?Environment?Programme'S Principles On The Implementation Of Sustainable Tourism Globally Are Presented Including Issue Like?Integration?Of Tourism Into Overall?Policy?For Development Of Sustainable Tourism And Its Integrated Management And Conditions For Success. .The Book Covers In Detail The?Convention?On?Biological?Diversity'S Sustainable Tourism Development Guidelines, Including The Guidelines For?Biodiversity?Conservation And Development Of Vulnerable Ecosystems, Concerned Policymaking, Development Planning And Management Processes And The Notification Processes And Information Requirements. Emphasis Also Lies On The Scope, Education, Capacity Building And Awareness Raising Aspects.The Last Chapter Of This Useful Reference Book Covers The Various Resolutions, Remarks, Declarations And?Summit?Reports On Global?Ecotourism?Like The Famous Quebec Declaration On Ecotourism; The Report On World Ecotourism Summit, Covering Aspects Of Ecotourism Planning, Regulation,?Product?Development,?Marketing?And Promotion. Issues Related To Monitoring Aspects Of Ecotourism Costs And Benefits Are Covered.The Information Contained In The Book Will Be Very Beneficial For All The Sectors Dealing With Tourism, Sustainable Tourism And Ecotourism Related Activities.
Keywords: Eco-Tourism